Cobalt Implant Composite (CIC) - Shamsul Baharin, Jamaludin, Prof. Dr.; Che Mohd. Ruzaidi, Ghazali, Prof. Madya; Nurhidayah, Ahmad Zaidi; Mazlee, Mohd. Noor (Ministry of Higher Education (MOHE), 2010)
Prof. Dr. Shamsul Baharin Jamaludin and his team from School of Materials Engineering won bronze for Cobalt Implant Composite (CIC). IPTA R&D Expo 2005, 30th September - 2nd October 2005 was held at Putra World Trade Center (PWTC), Kuala Lumpur.